Application Of Spectrogram In Analysing Electromyography (EMG) Signals Of Manual Lifting - Tengku Zawawi , Tengku Nor Shuhada; Abdullah, Abdul Rahim; Halim, Isa; Shair, Ezreen Farina; Mohamad Saleh, Saleha (Asian Research Publishing Network (ARPN), 2016)
-